Selection Decision Support System Pon Hockey Athletes Central Java Contingent Using Ahp And Promethee Methods - Afif Setyo Nugroho (Institute of Computer Science (IOCS), 2020)
Hockey is one of the sports that will be competed in the National Sports Week (PON). In the selection process for the Central Java contingent hockey athletes involved many criteria that were assessed, so that in the selection a multi-criteria decision support system was needed for more objective results. The method used in the decision support system for the selection of the Central Java contingent hockey athletes is a combination of the AHP method and the Promethee method. The AHP method is used to weight the criteria and test the consistency of the pairwise comparison matrix, while the Promethee method is used to rank in determining the best alternative. The purpose of the study was to determine the design and build a decision support system for the selection of Central Java contingent PON hockey athletes using a combination of AHP and Promethee methods, and to find out the results of implementing a combination of AHP and Promethee methods of decision support for the selection of PON hockey athletes from the Central Java contingent. The result obtained is a decision support system that has the output of a hockey athlete ranking from the highest net flow value to the lowest net flow value. From the ranking results, it was found that male hockey athletes who had the highest score were athletes with code A3 with a value of 0.564 and female hockey athletes who had the highest score were athletes with code A23 with a value of 0.172,